APPLICATION MODELING BASED CAD / CAM-SYSTEMS THE PRODUCTION OF GAS TURBINE ENGINES SHOULDER-BLADES - Гуцал, А.; Дубровський, С.; Ковешніков, М.; Петрук, Я.; Рубаненко, В. (Science-based technologies, 2011)
Possibilities  of  applying  are  considered  in  industry  of design on  a  base  CAD/CAM-system,  with  the  ground  of practical value for aircraft building enterprises. On a base CAD/CAM-system is offered methodology of receipt of shoulder-blade of compressor.